BUSINESS MANAGEMENT: JOINT VENTURE STRATEGIES AND BRAND EXPANSION IN A GLOBALIZED SCENARIO - Diego Weber dos Santos, Jean (Revista Gênero e Interdisciplinaridade, 2026)
This article explores the intersection between business management, the formation of joint ventures, and brand expansion strategies in an increasingly globalized market. Through a comprehensive literature review, the study analyzes how joint ventures function as a strategic mechanism for entering new markets, sharing risks, and accessing resources. Additionally, the complexities of international brand expansion are discussed, including the need for cultural adaptation and the choice of appropriate entry models. The article concludes that success in joint venture initiatives and brand expansion depends on careful strategic management, alignment of objectives between partners, and a deep understanding of target markets. The references used are strictly academic and from reliable sources to guarantee the validity of the conclusions presented.